An Exploration of the Factors Influencing the Use of Politeness Strategies in the EFL Classroom - Sutyrajmi Sutyrajmi S; Murni Mahmud; Sukardi Weda (Hasanuddin University, 2025)
Politeness plays a vital role in social interaction, as it reflects cultural norms, social relationships, and the speaker’s communicative intentions. This study aims to explore and analyze the factors that influence the use of politeness strategies in both spoken and written forms of communication. A qualitative descriptive approach was employed, with data collected through observations, interviews, and document analysis across various communicative settings, The findings indicate that several key elements such as social status, interpersonal distance, The researcher also found the factors that influence the use of politeness strategies based on Brown and Levinson’s theory. They are pay-off in 10 times and relevant circumstances in 6 times (social distance in 1 time, relative power in 5 times). Pay-off was the highest of the factor that influence the use of politeness strategies. These insights are expected to support the development of pragmatic theory and foster greater awareness of polite language use in diverse communicative contexts.